Seeding the idea of encapsulating a representative synthetic metagenome in a single yeast cell - Ignacio Belda (Nature Portfolio, 2021)
Synthetic metagenomics could potentially unravel the complexities of microbial ecosystems by revealing the simplicity of microbial communities captured in a single cell. Conceptionally, a yeast cell carrying a representative synthetic metagenome could uncover the complexity of multi-species interactions, illustrated here with wine ferments.